More Debits Than Credits: The Burnt Investor's Guide to Financial Statements. - Thomas, Arthur L. (The Accounting Review, 1976)
Reviews the book "More Debits Than Credits: The Burnt Investor's Guide to Financial Statements," by Abraham J. Briloff.